Who really killed Cock Robin? : an eco mystery - George, Jean Craighead, 1919- (New York : HarperTrophy, 1992)
Eighth-grader Tony Isidoro follows a trail of environmental clues to try and figure out what ecological imbalances might have caused the death of the town's best-known robin.
Elem. School Library Collection.
6.1
5-8
Keywords: Ecology -- Fiction; Environmental protection -- Fiction; Robins -- Fiction; Ecology -- Fiction; Environmental protection -- Fiction; Robins -- Fiction